Optimizing EFL Learners’ Writing Skills through Reflective Journaling - Wijaya, Kristian Florensio (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
AbstractIntegrating an in-depth reflective activity is pivotal in these modern second language writing learning enterprises. In the light of a profound writing learning reflection, EFL learners can pave more rewarding and promising writing trajectories as they are aware of their specific writing strengths and weaknesses. Concerning this statement, previous researchers contended that reflective journaling played an essential role in escalating EFL learners’ writing competencies since they are acclimatized to share their writing learning experiences in their journals genuinely. This small-scale library study aimed to investigate whether reflective journaling could optimize EFL learners’ writing skills. A thematic analysis while analyzing some relevant findings obtained from 30 previous reflective journaling and writing journal articles. By releasing this research action, the researcher is more likely to generate more robust credible findings as each identical results were grouped into some major themes. The thematically categorized research results unveiled that: (1) Reflective journaling increased EFL learners’ writing learning readiness, and (2) reflective journaling enabled EFL learners to be more resourceful writers. From the above-depicted research outcomes, second language educationalists are suggested to activate reflective journaling at the commencement of their regular writing learning enterprises to promote more interactive, innovative, and meaningful writing activities for language learners.Keywords: writing, reflective journaling, EFL learners, library study, thematic analysis